Remittances during crises: Evidence from ex‐Yugoslavia1. Issue 3 (3rd June 2016) - Koczan, Zsoka
Abstract: This paper begins by examining the characteristics and determinants of remittances sent from Germany to ex‐Yugoslavia, and then takes a first look at how they were affected by the war and later political and economic crises in the first half of the 1990s. The findings tentatively suggest that the propensity to send among ex‐Yugoslavs increased in the early 1990s, despite a breakdown in formal remittance channels and in contrast with the roughly stable and even decreasing propensity to send among Turkish guest workers.